Aiding Strategic Decision-Making to Improve Profitability Using Artificial Intelligence in Indian Small and Medium Enterprises - C, Vishwanathan (Digital Repository of Theses, 2025)
This dissertation focusses on the role of artificial intelligence (AI) to improve strategic decision making to improve profitability in the SMEs in India. With the Government of India envisioning doubling the Indian economy by 2025, the SME sector is vital to India's economy, serving as a key employer generator while contributing significantly to innovation. With stiff competition amongst the SMEs in India for growth and sustainability, SMEs also deal with resource constraints, financial constraints & the need to make quick and efficient decisions to make their organizations profitable. The study employed quantitative based and qualitative based techniques, while the literature review enabled the establishment whether there were any theoretical framework focusing on strategic decision-making, AI, and their intersection with industry standard performance frameworks like Balanced Score Card. The literature review identified the absence of a framework that brought about the use of AI in the Indian SME for strategic decisioning and improving profitability. The survey conducted among the participants from the Indian SMEs gathered data on their current AI adoption levels, perceived benefits of integrating AI for strategic decision making. Various statistical techniques-based evaluation of the data determined factors that played a key role in the use of Artificial Intelligence, Balanced Score Card for strategic decision making and their impact on improving profitability in Indian SMEs. The key findings indicate that AI has the potential to contribute significantly to improve decision-making and thereby leading to improved financial performance. However, the research also identified several barriers to AI adoption, including lack of awareness, lack of talent and skills, limited access to skilled personnel and the need for quality data and a robust data infrastructure. Thus, in order to stay ahead of their competition, the SMEs must carefully consider the integration of AI into their organization for strategic decisions and improve profitability. This integration must be done in a planned and focused manner as AI integration also comes with a higher cost around technology, skills and good quality data. The thesis recommends that SMEs should consider integrating AI, improving their data infrastructure to enable a better profitability, optimized resource allocation, and gain a competitive advantage over their competition.